NEW HORIZONS IN THE DIAGNOSIS OF VAGINITIS AND VAGINOSIS: MOLECULAR TECHNOLOGIES AND PROBIOTIC THERAPIES (CIPEEX, 2025)
Vaginal discharge remains one of the main gynecological complaints, characterized or not by associated symptoms such as leucorrhea, pruritus, dyspareunia, and unpleasant odor. However, due to excessive, unnecessary prescriptions and limited guidance on daily care, it is necessary to develop new diagnostic approaches, like propaedeutics, to prevent treatment resistance, which can render therapies ineffective when needed. Thus, the present study compiled information on the most up-to-date diagnostic methods for the treatment of vaginitis and vaginosis. Methodology: An integrative review was conducted using data from the PubMed and SciELO databases to identify studies on diagnostic techniques. Eleven articles were selected and analyzed according to inclusion and exclusion criteria. Results: Vaginitis caused by microorganisms such as Gardnerella vaginalis, Candida spp., and Trichomonas vaginalis is classified as specific. Vaginitis associated with imbalances in the vaginal microbiota, with proliferation of aerobic bacteria, is classified as nonspecific. Modern diagnostics include molecular methods, such as RT-PCR and NGS, which offer greater accuracy. The Immuno Quantex test assesses the local inflammatory response. Intravaginal devices containing hexylresorcinol and herbal extracts are effective in treating vaginal conditions. Probiotics, especially Lactobacillus crispatus, show promise in maintaining the microbiota and preventing infections, while new approaches to mixed vaginitis are under development to improve treatment and diagnostic efficacy. Conclusion: The combination of traditional treatments with new therapies, including probiotics and innovative medical devices, may provide a more comprehensive and effective solution for women experiencing recurrent vaginitis and other vaginal conditions.
Keywords: Clinical diagnosis; Gynecology; Treatment